1998
DOI: 10.1246/cl.1998.1025
|View full text |Cite
|
Sign up to set email alerts
|

Conformational and Orientational Switching of Uridine Derivatives by Borates

Abstract: We have demonstrated for the first time that the syn-anti orientation of 5′-amino-5′-deoxyuridine (1b) can readily be switched by adding borate as an extermal controlling factor. In borate added phosphate buffer, the syn/anti ratio of 1b dramatically increased with increasing borate concentration. This unique syn preference is most probably driven by the cooperative action of cyclic esterification of the 1b’s 2′,3′-cis-diol with borate and of hydrogen-bonding formation between 2-carbonyl oxygen and 5′-amino pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 18 publications
4
20
0
Order By: Relevance
“…[10] This is also consistent with the 1 H NMR analyses. However, results from CD experiments in acetonitrile clearly indicated that the 2', 3'-O-cyclic furanose ring, and a substitution at the 5' position, induced the syn orientation for the glycosyl group in Compound 2.…”
Section: Resultssupporting
confidence: 89%
“…[10] This is also consistent with the 1 H NMR analyses. However, results from CD experiments in acetonitrile clearly indicated that the 2', 3'-O-cyclic furanose ring, and a substitution at the 5' position, induced the syn orientation for the glycosyl group in Compound 2.…”
Section: Resultssupporting
confidence: 89%
“…The azide 6 was prepared in a yield of 80% from 1 by tosylation to 4, followed by reaction with NaN 3 [23] [24]. To obtain the acetamide 7, we hydrogenated 6 in the presence of Pd/C and Ac 2 O [24] [25], while treatment of the p-toluenesulfonate 4 with EtNH 2 in DMF gave 85% of the crystalline ethylamine 5 (m.p. 191 -1938) 2 ).…”
mentioning
confidence: 99%
“…35). 137,138 This switching-orientation strategy was latter applied to a series of peptidyl-ribonucleic acids (PRNAs), in which the 5 0 -amino-5 0 -deoxypyrimidine ribonucleoside moiety was appended to a mono-or oligo(g-L-glutamic acid) backbone through the 5 0 -amino group (62, Fig. 36).…”
Section: Interaction At the Saccharide Moietymentioning
confidence: 99%
“…The syntheses of 3 0 -aminocyanoborane-2 0 ,3 0 -dideoxythymidine (137) and 3 0 -aminocyanoborane-2 0 ,3 0 -dideoxyuridine (138) have been reported and their cytotoxic activities have been determined (Fig. 58).…”
Section: Modification Of the Saccharide Moietymentioning
confidence: 99%